Pressure Detection With Mach–Zehnder Linearized Tunable Diode-Laser Absorption Spectroscopy - Raoul-Amadeus Lorbeer; Matthias Bittner; Oliver Kliebisch; Peter Mahnke (IEEE Open Journal of Instrumentation and Measurement)
Tunable diode-laser absorption spectroscopy (TDLAS) sensors have shown to be applicable to, e.g., temperature and pressure measurements in gases. These parameters are indispensable in modern avionics. Even though these systems performed well in laboratory or closed environments, the harsh conditions of avionic flight introduce sources of error. To cope with these challenges, altered variants of the classical direct TDLAS may be taken into consideration. Here, we investigate the differences between an all fiber direct TDLAS and a Mach-Zehnder-based amplitude modulated TDLAS variant. We are able to demonstrate the increased noise immunity of the amplitude modulated system as well as the use of the oxygen A-band for the use as an optical pressure detector.